Assessment of immunization status of 12 to 23 months old children in rural Patna - Rahman, Ayesha K.; Raazi, Jamil (International Journal Of Community Medicine And Public Health, 2019)
Background: For immunization to be effective in decreasing the cases of vaccine preventable diseases and deaths, every child needs to be fully immunized. The present study was conducted with an objective to assess the immunization status and vaccination coverage of 12-23 months old children in the rural areas of Patna district. Methods: A community-based cross-sectional survey was conducted in the rural areas of Patna. The study was conducted using 30 cluster technique. The proforma designed by UNICEF was used as a study tool. Results: The vaccination coverage for bacille calmette guerin, pentavalent 1, 2 and 3 and measles were respectively 93.63%, 98.18%, 90%, 84.54% and 76.36%. The proportions of fully immunized children were 80.90%, partially immunized 19.10% and no unimmunized children. The dropout rate was 9.7% for BCG-DPT3, 14.56% for BCG-Measles and 13.83% for DPT1-DPT3. Conclusions: Although the vaccination coverage shows higher coverage but the dropout rates are still more than acceptable standards.